ACHINOS: a multi-anode read-out for position reconstruction and tracking with spherical proportional counters. (1st August 2022) - Katsioulas, I.; Knights, P.; Manthos, I.; Matthews, J.; Neep, T.; Nikolopoulos, K.; Ward, R.
Abstract: The spherical proportional counter is a versatile gaseous detector with physics applications ranging from rare event searches to fast neutron spectroscopy. In its simplest form, the detector operates with a single channel read-out, and uses pulse-shape information to reconstruct the interaction radius, which is used for background discrimination and target volume definition. Recent developments in the read-out instrumentation have enabled the use of a multi-anode read-out structure, ACHINOS. The multiple anodes provide information about the interaction position which, coupled with the radial information, can be used to reconstruct an ionisation track. This ability has implications for several applications of the detector, for example, enhanced background discrimination in rare event searches.